The Importance of Empathy in Maternal Healthcare Delivery - Agbi, Fortune Afi; Lulin, Zhou; Asamoah, Eric Owusu; Kissi, Jonathan (American Journal of Social Sciences and Humanities, 2022)
A woman's vulnerability is never greater than during pregnancy, childbirth, and the postnatal period. Quality healthcare delivery rest on actual interactions between patients and providers. Empathy has been acknowledged as a crucial component of patient care, benefiting both patients and medical staff. The patient-centered approach is considered an effective strategy to deliver successful patient care when healthcare professionals are more sensitive and attentive to the requirements of patients. Empathy means sharing another person's feelings and showing kindness to alleviate their misery or anguish. It is widely acknowledged as the essential component of nursing and midwifery care and regarded as the component of quality care. However, because it varies from practitioner to practitioner and from patient to patient, it is difficult to understand how compassion presents itself in the delivery of treatment. Midwives' compassionate attitudes and actions have a direct impact on obstetric outcomes. Even though scholars are studying the concept of empathy in nursing, little is known about what empathy in midwifery entails and how patients see it. Many advantages for patient communication, patient satisfaction, and treatment adherence are linked to healthcare professionals' empathy. This paper aims to examine the works of literature on the concept of empathy and highlight how crucial it is to provide care in the context of maternal healthcare.